Synthesis and performance of polycarboxylate superplasticisers with different propylene oxide contents. Issue 5 (16th March 2018) - Fan, Shimin; Wang, Tao; Qi, Shuai; Ma, Jianfeng; Huang, Zhen; Chen, Jian; Ran, Qianping
Abstract : A series of polycarboxylate superplasticisers (PCEs) were synthesised by the random free radical polymerisation of acrylic acid (AA) and polyether containing different propylene oxide (PO) contents. The structures of the polymers were confirmed by gel permeation chromatography, hydrogen-1 nuclear magnetic resonance and infrared spectroscopy. The influence of the PCEs with different PO contents on the dispersion, adsorption, hydration and fluidity retaining abilities of cement pastes was investigated. The results indicated that the PCEs containing PO units exhibited a similar initial cement paste fluidity and better slump retaining ability. The adsorption experiments were consistent with the cement paste tests. The PCEs showed similar initial adsorption amounts at different dosages. The PCEs with PO content, however, especially with higher PO content, exhibited obviously lower adsorption amounts over time at the dosage of 2·5 mg/g. In addition, the PO units in the PCEs demonstrated a weaker effect on cement hydration.